Analisis penerapan akuntansi pertanggungjawaban sebagai alat penilaian kinerja manajer pusat biaya pada Hotel Biz Manado - Winowoda, Sabrina Sheren; Alexander, Stanly W.; Tangkuman, Steven J. (Manajemen Bisnis dan Keuangan Korporat, 2024)
Responsibility accounting is an effective accounting system used to accurately measure and evaluate the activities of responsibility centre managers within a company. It is based on comprehensive information available at each responsibility centre. This study will determine how responsibility accounting should be applied in assessing the performance of cost centre managers at Hotel Biz Manado. This research was conducted using a qualitative approach with a descriptive analysis method. We used two data collection techniques: interviews and documentation. This study shows that Hotel Biz Manado has successfully implemented responsibility accounting. They have an organisational structure, budget planning, account code classification, and accountability reports. However, they still need to classify controllable and uncontrollable costs in their reports. Overall, Hotel Biz Manado performs well in their cost centre. They excel in their work and planning process, as well as in controlling and realising costs.